Предмет: Алгебра,
автор: artem00200
Доказать тождество : a^3-a^2-a+1=(a-1)^2(a+1)
Ответы
Автор ответа:
0
а³-а²-а+1=(а-1)²(а+1)
а³-а²-а+1=(а²-2а+1)(а+1)
а³-а²-а+1=а³-2а²+а+а²-2а+1
а³-а²-а+1=а³-а²-а+1
т к оба выражения одинаковые тождество доказано
а³-а²-а+1=(а²-2а+1)(а+1)
а³-а²-а+1=а³-2а²+а+а²-2а+1
а³-а²-а+1=а³-а²-а+1
т к оба выражения одинаковые тождество доказано
Автор ответа:
0
П.ч.=а³-а²-а+1
Л.ч.=(а-1)²(а+1)=(а²-2а+1)(а+1)=а³-2а²+а+а²-2а+1=а³-а²-а+1
П.ч.=Л.ч.
Тождество доказано.
Л.ч.=(а-1)²(а+1)=(а²-2а+1)(а+1)=а³-2а²+а+а²-2а+1=а³-а²-а+1
П.ч.=Л.ч.
Тождество доказано.
Похожие вопросы
Предмет: Литература,
автор: YatoHiyori
Предмет: Математика,
автор: asylbekulaszan16
Предмет: Английский язык,
автор: Аноним
Предмет: Литература,
автор: 130620001
Предмет: География,
автор: растофарри